Um estudo da estabilidade de pórticos considerando o fator do comprimento efetivo e as forças nocionais - Alex de Barros (2010)
The objective of this work is to study the steel frames stability considering the application of the effective length factor and notional loads in the analysis of these structures. To achieve this goal, the characteristics of the effective length method are discussed, showing the advantages and disadvantages of its application. The concept of story buckling approach is presented, as well as considerations for determining the K-factor in the inelastic phase. In this work, the concept of the formulation based on the notional loads, to consider the geometrical and material imperfections from the application of a fictitious horizontal force corresponding to a fraction of the sum of all vertical forces acting on the story is discussed. These methods are comparatively evaluated on the basis of a program written in FORTRAN 90 that was developed to perform an advanced inelastic analysis of plane steel frames. Examples are presented for comparison of different methodologies as well as evaluating the procedures of ABNT NBR 8800: 2008.